2016
DOI: 10.3390/met6070154
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-Nickel-Boron Supported over Polypyrrole-Derived Activated Carbon for Hydrolysis of Ammonia Borane

Abstract: Abstract:In this study, polypyrrole (PPy) nanofibers were used to synthesize a super-activated carbon material. A highly-dispersed Co-Ni-B catalyst was supported on PPy nanofiber-derived activated carbon (PAC) by chemical reduction. The Co-Ni-B/PAC hybrid catalyst exhibited excellent catalytic performance for the decomposition of ammonia borane (AB) in an aqueous alkaline solution at room temperature. The size of the metal particles, morphology of Co-Ni-B/PAC, and catalytic activity of the supported catalyst w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…91 For example, Yurderi et al , 92 Bulut et al 93 and Kazici et al 94 used activated carbon (purchased from Sigma-Aldrich) as a support to load active species as catalysts for the dehydrogenation of ammonia-borane. Zou et al 95 reported polypyrrole derived activated carbon as a support to load Co–Ni–B for AB hydrolysis. Biomass is one of the raw materials commonly used to prepare activated carbon.…”
Section: Porous Materials Supported Metal Catalystsmentioning
confidence: 99%
“…91 For example, Yurderi et al , 92 Bulut et al 93 and Kazici et al 94 used activated carbon (purchased from Sigma-Aldrich) as a support to load active species as catalysts for the dehydrogenation of ammonia-borane. Zou et al 95 reported polypyrrole derived activated carbon as a support to load Co–Ni–B for AB hydrolysis. Biomass is one of the raw materials commonly used to prepare activated carbon.…”
Section: Porous Materials Supported Metal Catalystsmentioning
confidence: 99%